CODES OF ETHICS AS A MARKETING COMMUNICATION TOOL: THE IMPACT OF CODES OF ETHICS ON THE BEHAVIOUR AND APPEARANCE OF EMPLOYEES - Kozáková, Jana; Savov, Radovan; Darázs, Tamás (Communication Today, 2024)
Codes of ethics are crucial in communicating and building the values of organisations and their employees. This research study focuses on exploring various aspects of ethical behaviour and the impact of ethical constraints on employee performance in organisations. In the context of the growing importance of business ethics and human resource management, this study statistically identifies differences between organisations based on their ethical characteristics and strategies. The integration of ethics into corporate strategy is found to have an impact on the permissible behaviour and appearance of employees, with past ethical scandals leading to more stringent measures. In addition, the length and updating of the code of ethics affect the control over certain aspects of employee behaviour. These results underscore the importance of codes of ethics as tools for communication as well as for managing employee ethics and behaviour. They also highlight the role of multinational corporations in the diffusion of these practices and their impact on smaller market players, as well as the importance of managing workplace constraints. In conclusion, this study contributes to a deeper understanding of ethical practices and their importance within organisations.